FOREIGN CAPITAL INFLOWS AND ECONOMIC GROWTH IN SAARC - Idrees, M.A. (University of Jaffna, 2018)
The purpose of the study is to find out the impact of foreign debt, foreign portfolio investment, foreign direct investment, foreign remittance and foreign import on economic development. For this purpose, we use data from 1992 to 2015 from World Bank sites of the selected SAARC countries namely Pakistan, India, Bangladesh, and Sri Lanka. An Econometric view tool is applied to find out impact of independent and dependent variable. For this Panel Unit Root test, Panel co-integration test, panel regression model (Fixed or random effect) and granger causality is used. The findings of panel unit root test are showing that the variables are not stationary at level but at first level all variables are stationary. Panel co-integration test shows the long relationship among variables. Foreign Imports, Foreign direct investment and foreign remittance have positive impact on GDP, whereas foreign portfolio investment and foreign debt have negative impact on GDP. Lastly Granger causality shows that FDI, FD and FI have unidirectional relation but FR and FPI doesn’t have any relation.
Keywords: gross domestic product; foreign direct investment; foreign debt; foreign portfolio investment foreign imports; foreign remittance & SAARC